Precise tuning of interlayer electronic coupling in layered conductive metal-organic frameworks - Lu, Yang; Zhang, Yingying; Yang, Chi-Yuan; Revuelta, Sergio; Qi, Haoyuan; Huang, Chuanhui; Jin, Wenlong; Li, Zichao; Vega-Mayoral, Victor; Liu, Yannan; Huang, Xing; Pohl, Darius; et al. (Nature Communications, 2022)
Two-dimensional conjugated metal-organic frameworks (2D c-MOFs) have attracted increasing interests for (opto)-electronics and spintronics. They generally consist of van der Waals stacked layers and exhibit layer-depended electronic properties. While considerable efforts have been made to regulate the charge transport within a layer, precise control of electronic coupling between layers has not yet been achieved. Herein, we report a strategy to precisely tune interlayer charge transport in 2D c-MOFs via side-chain induced control of the layer spacing. We design hexaiminotriindole ligands allowing programmed functionalization with tailored alkyl chains (HATI_CX, X = 1,3,4; X refers to the carbon numbers of the alkyl chains) for the synthesis of semiconducting Ni3(HATI_CX)2. The layer spacing of these MOFs can be precisely varied from 3.40 to 3.70 Å, leading to widened band gap, suppressed carrier mobilities, and significant improvement of the Seebeck coefficient. With this demonstration, we further achieve a record-high thermoelectric power factor of 68 ± 3 nW m−1 K−2 in Ni3(HATI_C3)2, superior to the reported holes-dominated MOFs.
CRIS-Team Scopus Importer:2023-03-20